Peran Dewan Pendidikan Dalam Meningkatkan Mutu Pendidikan Di Kabupaten Rejang Lebong - Lukman Asha (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Improving the quality of education is the responsibility of all parties. One of the institutions carrying out this mandate in an area is the Education Council. This study aims to find out how the role of the Education Council in Rejang Lebong Regency in improving the quality of education so far. Through observation and interviews, it was found that the role of the Education Council in improving the quality of education in Rejang Lebong Regency was as follows: (a) consideration in determining and implementing education policies, (b) supporting both tangible financial, thought and energy in the implementation of education (c) controllers in the context of transparency and accountability in the administration and output of education, (d) mediators between the government and the Regional People's Representative Council (DPRD) with the community